SPE Oil and Gas India Conference and Exhibition 2010
DOI: 10.2118/127422-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cement-Sheath Wellbore Integrity for CO2 Injection and Storage Wells

Abstract: It is critical that CO2 injection and storage wells have wellbore integrity to help prevent leakage of CO2 during the injection period, as well as long-term zonal isolation to sustain the loading conditions of pressure testing, completions, injection, shut-in, and stimulation treatment. This paper highlights the salient engineering design features of planning a successful cementing-job operation for extended-reach drilled (ERD), carbon capture and storage (CCS) wells. Corrosion in Portland cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Twenty years ago, one million metric tons of carbon dioxide were injected annually into the North Sea aquifer [44]. Canada and Algeria sequestrated over 20 million tons (Mt) of CO 2 in their deep geological sites [150,151]. However, there have been a few issues raised in recent years, indicating the potential leakages paths created during CO 2 geological storage.…”
Section: Leakage Paths and Risk Analysis Of Co 2 Geological Storagementioning
confidence: 99%
“…Twenty years ago, one million metric tons of carbon dioxide were injected annually into the North Sea aquifer [44]. Canada and Algeria sequestrated over 20 million tons (Mt) of CO 2 in their deep geological sites [150,151]. However, there have been a few issues raised in recent years, indicating the potential leakages paths created during CO 2 geological storage.…”
Section: Leakage Paths and Risk Analysis Of Co 2 Geological Storagementioning
confidence: 99%
“…Shadravan 37 found that the cement ring would reach its yield limit and fail after several cycles of loading. Philippacopoulos and Berndt, 38 Gray et al, 39 Bosma, 40 Takase, 41 and others established thermal‐elastic models of the cement ring using finite element software and believed that temperature decrease would cause the interface of the cement ring to stretch and debond, while temperature increase would cause the shear failure of the cement ring. The wellbore is a combination of the casing cement ring (the first interface) and the cemented wellbore (the second interface).…”
Section: Introductionmentioning
confidence: 99%
“…This process is named as chemical degradation (Bruckdorfer, 1986). When a water injection well or oil production well is converted to CO 2 injection well, the high injection pressure will result to the mechanical failure of the cement sheath (Takase et al, 2010). Cement sheath of a CO 2 injection well is vulnerable due to the chemical degradation and mechanical disruption.…”
Section: Introductionmentioning
confidence: 99%